Doubling the single-dose infusion rate of tocilizumab in rheumatoid arthritis is safe and efficacious. (3rd July 2016) - Lindegaard, HM; Johansen, P; Gröndal, G; Jensen, EC; Juul, L; Schlemmer, AM; Agular, B; Hansen, IMJ
Abstract : Objectives : To investigate the impact of enhanced infusion rate of tocilizumab on the occurrence of infusion reactions, overall safety, and efficacy in rheumatoid arthritis (RA). Method : We conducted a 24-week multicentre, open-label, randomized parallel group study comparing adverse event (AE) and effect profiles following tocilizumab IV 8 mg/kg every 4 weeks over 31 min vs. standard 60-min infusions in patients with RA and an inadequate clinical response to disease-modifying anti-rheumatic drugs (DMARDs) and/or tumour necrosis factor (TNF)-α inhibitors. Results : A total of 47 patients were enrolled in the study and randomized to fast infusions (n = 25) and controls (n = 22). Incidences of infusion reactions were similar between the two groups, neither of them leading to withdrawal. Likewise, the incidence of additional AEs did not differ between the treatment arms. Two serious adverse events (SAEs) were reported, in the control group. Four patients withdrew due to AEs, two from each arm. Efficacy at week 24 was comparable between groups. Conclusions : In RA, monthly tocilizumab infusions of 8 mg/kg provided over 31 or 60 min during 24 weeks did not differ concerning safety or efficacy.